IMPLEMENTASI AKAD MUSYARAKAH DALAM PENDANAAN CROWDFUNDING SYARIAH UNTUK MENDUKUNG PENGEMBANGAN UMKM - Fatikah, Berliana Haza; Fathurohman SW, Oman (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
This research examines the application of the Musyarakah contract in sharia-compliant crowdfunding services as an alternative financing solution for micro, small, and medium enterprises (MSMEs). Sharia crowdfunding, grounded in Islamic principles, provides an inclusive funding mechanism for MSMEs by eliminating elements of usury (riba) and uncertainty (gharar), while ensuring transparency in fund management. The Musyarakah Musahamah agreement, structured as a partnership with proportional profit-and-loss sharing based on capital contributions, is identified as a financing model that aligns well with the needs and characteristics of MSMEs. This research also explores the implementation of this contract, focusing on adherence to sharia principles and transparency in management. Through a literature review and thematic analysis, the study finds that the application of the Musyarakah Musahamah contract in Islamic crowdfunding enhances access to funding for MSMEs, fosters equitable collaboration between investors and entrepreneurs, and has the potential to create a more inclusive and sustainable economic ecosystem. This research underscores the importance of collaboration among regulators, crowdfunding platforms, and MSME stakeholders to optimize the implementation of sharia contracts in promoting economic growth. Keyword : Musyarakah Akad, Crowdfunding, MSME, Financing